Biodegradation of Diethyl Phthalate (DEP) Compound Using Fungi Isolated from Leachate Water of Tpa Sarimukti Bandung - Suci Keiva Mulyana*; Emenda Sembiring (Riwayat: Educational Journal of History and Humanities, 2023)
Industrial development in Indonesia increases every year. Industries that grow significantly every year are the food, beverage and household furniture industries, which almost all of their packaging uses plastic materials. One of the dangerous and toxic materials in plastic manufacturing is phthalate. One phthalate compound that is commonly found in everyday life is diethyl phthalate (DEP). This compound is dangerous because it is carcinogenic, xenoestrogenic and its effect on the endocrine disrupts the binding and action of natural hormones, thus disrupting physiological processes. The accumulation of plastic in the landfill causes this compound to be identified in leachate with an existing concentration of 2.4 mg/L. Biological treatment is one of the appropriate technologies in DEP removal. The treatment is carried out by removing DEP using fungus isolated in the leachate water sampled. The mechanism of phthalate degradation by fungi can be explained simply where fungi use phthalates as the only source of carbon and energy for their growth. Degradation tests were carried out on Malt Extract Broth (MEB) liquid media to which phthalate was added at existing concentrations and using selected efficient fungi over a period of 6 days. Concentration testing was carried out by analysis using High Performance Liquid Chromatography (HPLC). Analysis of fungal cell count using spectrophotometric method by measuring OD value. Tests were carried out on days 0, 2, 4 and 6; Fungi from leachate water that have the potential to degrade DEP compounds include Aspergillus Niger, Penicillium sp and Trichoderma sp